Design and performance of embankments on very soft soils - Almeida, Marcio (Marcio S. S.); Marques, Maria Esther Soares (Huesker series engineering with geosynthetics, 2013)
Embankment construction projects on very soft soil often give rise to serious problems. This volume on geotechnics and soft soil engineering therefore treats all phases of the design and construction process exhaustively, from the first investigation step to the monitoring of constructed work. The book presents the development concepts necessary for the project stages and discusses in great detail construction methods, displacement estimations, stability analyses, monitoring, and various other aspects involved.